KNOWLEDGE ON MANAGEMENT OF FOOD IMPACTION IN PROSTHESES - Prakash, Satya; Ganapathy, Dhanraj; Ramanathan , Visalakshi (International Journal of Psychosocial Rehabilitation, 2019)
Food impaction is one of the common complaints reported by the patients wearing dental prostheses. It also leads to caries of the abutment and the adjacent teeth leading to subsequent failure of the prostheses. AIM To assess the knowledge, attitude and opinion of dental practitioners regarding the effect and management of food impaction around dental prostheses. MATERIALS AND METHOD A close ended questionnaire comprising of 10 questions regarding occurrence, consequences, likely reason and most routinely followed line of treatment for food impaction was distributed to 100 dental practitioners and responses recorded. The data were tabulated and analysed. RESULTS Majority of the practitioners(87.1%) were aware and some of them(13.9%) were unaware regarding the causes, effect and management of food impaction in various prostheses. Most of the respondents had come across patients who complained of food impaction. The most common consequences of food impaction was proximal caries. CONCLUSION Majority of the dentists considered poor marginal adaptation of the crown as the most likely reason for food impaction. Repeating the prostheses with emphasis on prescribing and reinforcing the use of proper interdental aids was considered as the ideal treatment option.